D186/D190 is an allele-dependent determinant of HIV-1 Nef function - Imle, Andrea; Stolp-Rastätter, Bettina; Fackler, Oliver Till (Virology, 2016)
The HIV-1 pathogenesis factor Nef interacts with numerous ligands to affect cellular vesicular transport, signal transduction and cytoskeletal dynamics. While most Nef functions depend on multivalent protein interaction motifs, disrupting actin dynamics requires a motif that specifically recruits the host kinase PAK2. An adjacent aspartate was recently predicted to mediate Nef-β-catenin interactions. We report here that β-catenin can be co-immunoprecipitated with Nef.GFP from Jurkat T cell lysates. This association is conserved among lentiviral Nef proteins but does not involve classical Nef protein interaction motifs, including the critical aspartate. While aspartate-to-alanine mutations impaired cell surface receptor downregulation and interference with actin dynamics and cell motility by HIV-1 NA7 Nef, analogous mutations did not affect HIV-1 SF2 Nef function. These allelic differences were determined by a proximal lysine/arginine polymorphism. These results emphasize differences between Nef alleles regarding the functional role of individual residues and underscore the need for allele-specific structure-function analyses.